2000
DOI: 10.1128/iai.68.4.1760-1764.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immune Profile of Nonhealing Cutaneous Leishmaniasis Patients with Those with Active Lesions and Those Who Have Recovered from Infection

Abstract: Th1-type cellular immune responses play a critical role in protection against infection with Leishmania parasites, whereas activation of Th2-type cells results in progressive disease. Cutaneous leishmaniasis caused by Leishmania major is often a self-healing disease; however, persistent nonhealing forms are also known. In the present study, we have described cell-mediated immune responses in nonhealing patients by measuring T-cell proliferation, cytokine production, and phenotypic characterization of these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
5
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 29 publications
4
84
5
1
Order By: Relevance
“…A resposta tipo 2 gera aumento de IL4, que estimula a diferenciação de linfócitos B, ocasionado aumento na produção de anticorpos. Este padrão encontra-se associado comumente a pacientes com doença severa 1 . A utilização da resposta humoral no diagnóstico da infecção tegumentar, portanto, permanece controverso pela baixa quantidade de anticorpos séricos detectáveis pelos métodos tradicionais e pela infinidade de reações cruzadas observadas principalmente nas técnicas imunoenzimáticas devido a sua sensibilidade acentuada.…”
Section: Discussionunclassified
“…A resposta tipo 2 gera aumento de IL4, que estimula a diferenciação de linfócitos B, ocasionado aumento na produção de anticorpos. Este padrão encontra-se associado comumente a pacientes com doença severa 1 . A utilização da resposta humoral no diagnóstico da infecção tegumentar, portanto, permanece controverso pela baixa quantidade de anticorpos séricos detectáveis pelos métodos tradicionais e pela infinidade de reações cruzadas observadas principalmente nas técnicas imunoenzimáticas devido a sua sensibilidade acentuada.…”
Section: Discussionunclassified
“…Nonhealing lesions in humans infected with L. major, have been associated with low levels of IFN-␥ and high levels of IL-4 and, in contrast, healing lesions were associated with elevated levels of IFN-␥ and low levels of IL-4 (18) in PBMCs. IFN-␥, IL-1, IL12p40, TNF-␣, TGF-␤, and IL-10 mRNA were detected in the lesions of healing subjects, whereas IL-4 mRNA was only found in a few biopsies (19); in these cases, lesion healing was again associated with elevated levels of IFN-␥ and low levels of IL-4.…”
Section: Immunological and Genetic Evidence For A Crucial Role Of Il-mentioning
confidence: 96%
“…Phlebotomus longipes can not bite over the clothing, but bite the exposed areas of the body to suck the blood, so the lesions mainly appear in hands, face and legs (Nadim and Seyedi, 1971). Considering the fact that about 48.7% of patients had one or more skin lesions, we concluded that a sandfly, because of its physiologic characteristics, bites the host more than one time, and from every area of the bite, parasites enter the blood (Ahmadiyazdi et al, 2004;Yaghoobi et al, 2002;Ajdary et al, 2000).…”
Section: Discussionmentioning
confidence: 99%